PENGARUH TEKNIK SURVEY QUESTION READ REFLECT RECITE REVIEW (SQ4R) DAN TEKNIK SKEMA TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN MATA PELAJARAN BAHASA INDONESIA PADA SISWA SD NEGERI KELAS III DI KECAMATAN KARANGANYAR DEMAK - Sulikhah, Sulikhah; Utomo, Slamet; Santoso, Santoso (Universitas Muria Kudus, 2020)
The purpose of this study to determine the effect of Question Survey Technique Read Reflect Recite Review (SQ4R) Technique and Scheme Technique to improving comprehension reading skills of Indonesian language Lesson. The research is Quasy Experiment with the design of Non Equivalent Control Group Design. The population in this study were third grade students of Govermant Elementary School of KaranganyarDemak. Sampling technique used purposive sampling. The sample size were 40 respondents in SDN Undaan Kidul I and 40 respondents in SDN Cangkring B. This research instrument used a questionnaire. The data analysis technique used paired t test and Mann Whitney test. The results of the study get a score before the SQ4R action is 32.5% with the category of incomplete and 67.5% of the category of completion. Posttest stage gets a score of 87.92% with a good category (complete). In the Schema action get a score before the action 37.5% in the incomplete category and 62.5% in the complete category. In the posttest stage get a score of 80.75% with a good category (complete). The results of the Paired Samples T Test for SQ4R measures p value 0.004 and in the scheme (p 0.001) so that it shows the influence of Survey Question Read Reflect Recite Review (SQ4R) and Scheme techniques for increasing reading comprehension skills in Indonesian subjects. Mann Whitney analysis results obtained p 0,000, which shows the differences in the influence of Survey Question Read Reflect Recite Review (SQ4R) Techniques and Scheme Techniques on improving reading comprehension skills in Indonesian subjects.